Body Image Dissatisfaction, Breastfeeding Experiences, and Self-Efficacy in Postpartum Women with and Without Eating Disorder Symptoms. (November 2022) - Kapa, Hillary M.; Litteral, Jennifer L.; Keim, Sarah A.; Jackson, Jamie L.; Schofield, Kyle A.; Crerand, Canice E.
Background: Women during the postpartum period undergo significant changes which affect body image, eating behaviors, and, potentially, breastfeeding. There is limited research about relationships among these variables, particularly related to breastfeeding experiences and self-efficacy. Research Aims: To determine: (1) the associations between eating disorder symptoms and body image, breastfeeding self-efficacy, and breastfeeding experiences; and (2) the differences in body image, breastfeeding self-efficacy, breastfeeding experiences, and breastfeeding status of postpartum women with and without clinically significant eating disorder symptoms. Methods: A secondary data analysis using a 2-group correlational, cross-sectional online survey design was used. Participants with infants 2–6 months old who had breastfed their infant at least once ( N = 204) were recruited nationally to complete a cross-sectional survey assessing breastfeeding and postpartum physical and mental health using validated measures. Linear and logistic regression evaluated differences between participants with and without eating disorder symptoms regarding their body image, breastfeeding experience and self-efficacy, and breastfeeding status (continued vs. discontinued) at 2 months postpartum. Results: Clinical eating disorder symptoms were reported by 9.8% ( n = 20). Participants with clinical eating disorder symptoms reported lower appearance evaluations ( B = -0.53, 95% CI [-0.93, -0.14]) and body image satisfaction ( B = -0.55, 95% CI [-0.87, -0.23]); reduced odds of breastfeeding at 2 months postpartum (AOR = 0.15, 95% CI [0.04, 0.56]); and lower breastfeeding self-efficacy ( B = -7.70, 95% CI [-14.82, -0.58] relative to participants without clinical symptoms. No differences between groups were observed for breastfeeding experiences. Conclusions: Participants with clinically significant eating disorder symptoms are at risk for early breastfeeding discontinuation and lower breastfeeding self-efficacy. Our findings have implications for future research and clinical care practices, including screening for body image concerns and eating disorder symptoms and supporting breastfeeding self-efficacy.